2011
DOI: 10.1007/s11274-011-0925-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of marine bacteria capable of utilizing phthalate

Abstract: Eleven phthalate-degrading bacterial strains were isolated from seawater collected off the coast of Japan. The isolates were found to be most closely related to the marine bacterial genera Alteromonas, Citreicella, Marinomonas, Marinovum, Pelagibaca, Rhodovulum, Sulfitobacter, Thalassobius, Thalassococcus, Thalassospira, and Tropicibacter. For the first time, members of these genera were shown to be capable of growth on phthalate. The plate assay for visual detection of phthalate dioxygenase activity and PCR d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 24 publications
1
21
0
1
Order By: Relevance
“…HC degraders were not only cultivated after enrichment cultures on HC, but were also directly detected in the sediment and seawater samples, by sequencing of random DGGE bands. The sequencing of DGGE bands confirms that both sediment and seawater contain known HC degraders as Alcanivorax (alkanes) and Alteromonas (aromatics, Gutierrez et al, 2013) or putative, such as Thalassobius (Iwaki et al, 2012) and Thermoanaerobacterium, often dominant in methanogenic alkanes degrading enrichment culture microcosms (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
“…HC degraders were not only cultivated after enrichment cultures on HC, but were also directly detected in the sediment and seawater samples, by sequencing of random DGGE bands. The sequencing of DGGE bands confirms that both sediment and seawater contain known HC degraders as Alcanivorax (alkanes) and Alteromonas (aromatics, Gutierrez et al, 2013) or putative, such as Thalassobius (Iwaki et al, 2012) and Thermoanaerobacterium, often dominant in methanogenic alkanes degrading enrichment culture microcosms (Wang et al, 2014).…”
Section: Discussionmentioning
confidence: 58%
“…Thalassococcus has been shown to be capable of utilizing phthalate (Iwaki et al, 2012), but its ability to metabolize peptides, as suggested here, has not yet been explored. Previous studies have shown that Rhodobacterales are often one of the dominant groups in coastal seawaters, accounting for as high as 75% of the Alphaproteobacteria (Dong et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…Marine bacteria were collected from each seawater sample by filtration and resuspended in 30 mL of commercial artificial seawater medium Daigo's IMK-SP (Nihon Pharmaceutical, Osaka) [7]. Enrichment and purification of the strains were performed according to a previously described procedure with some modifications [7]; Daigo's IMK-SP medium was supplemented with 5 mM phenol.…”
Section: Isolation Of Phenol-degrading Bacteria From Seawatermentioning
confidence: 99%